The Development of Science Comic in Human Digestive System Topic for Junior High School Students - Nelah Roswati; Nuryani Y Rustaman; Ikmanda Nugraha (Journal of Science Learning, 2019)
The science education approach has covered by using printed teaching media. One of the popular printed press that most accessible and may used in science education is a comic book. However, it is sometimes difficult to find the ideal and the appropriate comic books that can be used as the instructional tool of science education, because most of them are inappropriate for learning science and did not fit with the readers’ culture. The purpose of this study is to develop and evaluate the Science comic to contribute to science learning about Human Digestive System Topic (HDST) concepts. In this study, a science comic book was created and implemented to 92 students of year eight from three different junior high schools and three science teachers as a subject implementation development. Students’ responses through the questionnaire and students-teachers’ implementation test sheets evaluated through qualitative content analysis. The model used for this study is design and development. The result shows, most of the students agreed that science comic book helps them to learn through simplifying science concept and understanding the topic more accessible. The ideal science comic should also follow the right steps, appropriate aspects consisted, gain more science experience for both students and teachers to enjoy the learning process.HighlightsScience comic is one of effective printed teaching mediaHumour can be illustrated by the narrative to transfer the information of scienceScience comic can cover the need to communicate the fascination, joy, and utility of science